Elevated Levels of Apelin-36 in Heart Failure Due to Chronic Systemic Hypoxia - Ferdinal, Frans; Limanan, David; Rini, Retno Dwi; Alexsandro, Rio; Helmi, Rizal (International Journal of Angiology, 2019)
Apelin is a novel adipokine identified as an endogenous ligand of the specific orphan receptor APJ. Among the various isoforms of apelin, an increase in the apelin-36 plasma level has been associated with oxidative stress, and this isoform has various biological effects, such as positive inotropic, vasodilatory, and antiatherosclerotic effects. Therefore, apelin-36 may be used as a biomarker of heart failure (HF). Advances in the understanding of the molecular mechanisms underlying HF cannot be achieved without the use of animal models. However, it is unclear whether chronic systemic hypoxia can cause HF in rats. The present study aimed to determine whether chronic systemic hypoxia can cause HF in rats and whether apelin-36 can be used as a biomarker of HF. The study included Sprague–Dawley rats. The rats were randomly divided into seven groups (n = 4). One of the groups was a control group, and the six other groups were exposed to hypoxia (8% O2) for different durations (6 hours, 1 day, 3 days, 5 days, 7 days, and 14 days). The exposure groups showed ventricular hypertrophy accompanied by myocardial structural damage, which indicated ventricular remodeling. In addition, the exposure groups showed elevated apelin-36 plasma levels and signs of oxidative stress. Moreover, gel electrophoresis of heart tissue showed five bands that corresponded to apelin isotypes, including apelin-36. In an experimental rat HF model with chronic systemic hypoxia, apelin-36 was elevated along with oxidative stress. Apelin-36 along with oxidative stress may serve as a biomarker of HF in this model.
Keywords: apelin-36; biomarker; heart failure; oxidative stress; MDA; GSH; protein carbonyl